2002
DOI: 10.2174/1389203023380422
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Phosphorylase as a Molecular Target for Type 2 Diabetes Therapy

Abstract: The regulation of the hepatic glucose output through glycogenolysis is an important target for type 2 diabetes therapy. Glycogenolysis is catalyzed in liver, muscle and brain by tissue specific isoforms of glycogen phosphorylase (GP). Because of its central role in glycogen metabolism, GP has been exploited as a model for structure-assisted design of potent inhibitors, which may be relevant to the control of blood glucose concentrations in type 2 diabetes. Several regulatory binding sites have been identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
11

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(101 citation statements)
references
References 0 publications
1
89
0
11
Order By: Relevance
“…Later, (3R,5S,6S,7E,9S)-megastigman-7-ene-3,5,6,9-tetrol-9-O-β-D-glucopyranoside (69) What's more, 1β,9α-dihydroxyeudesm-3-en-5β,6α,7α,11αH-12,6-olide (83) was isolated and identified from the fruits of C. pinnatifida [37]. In addition, six others were subsequently isolated from the leaves of C. pinnatifida, [35], and gibberellic acid (87) [38] (Figure 7). …”
Section: Monoterpenoids and Sesquiterpenoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, (3R,5S,6S,7E,9S)-megastigman-7-ene-3,5,6,9-tetrol-9-O-β-D-glucopyranoside (69) What's more, 1β,9α-dihydroxyeudesm-3-en-5β,6α,7α,11αH-12,6-olide (83) was isolated and identified from the fruits of C. pinnatifida [37]. In addition, six others were subsequently isolated from the leaves of C. pinnatifida, [35], and gibberellic acid (87) [38] (Figure 7). …”
Section: Monoterpenoids and Sesquiterpenoidsmentioning
confidence: 99%
“…Glycogenolysis is catalyzed in liver, muscle and brain by tissue specific isoforms of glycogen phosphorylase (GP). Because of its central role in glycogen metabolism, GP had been exploited as a model for structure assisted design of potent inhibitors, which might be relevant to the control of blood glucose concentrations in type II diabetes [87,88]. Maslinic acid isolated from C. pinnatifida was found to inhibit GP in moderate strength; the IC50 was 28 µmol/L.…”
Section: Endocrine System Effectsmentioning
confidence: 99%
“…Glycogen phosphorylases (existing as 'muscle', 'brain', or 'liver' isoforms) are allosterically regulated enzymes consisting of a dimeric arrangement of two identical subunits related to each other by a C2 symmetry. Protein crystallographic studies (Chrysina, 2010;Oikonomakos, 2002) revealed the existence of six binding sites in GP (Fig. 1): the catalytic, the inhibitor, the allosteric, the glycogen storage, and the new allosteric sites, as well as the newly discovered benzimidazole site (Chrysina et al, 2005).…”
Section: Glucose Analogue Inhibitors Of Glycogen Phosphorylasementioning
confidence: 99%
“…A possible mechanism for the inactivation of phosphorylase is through changes in the concentrations of metabolites that bind to phosphorylase. Allosteric ligands of phosphorylase, such as glucose and glucose 6-phosphate, which favour the T (tense) conformation, cause dephosphorylation (inactivation) because the T state is a better substrate for dephosphorylation than the relaxed (R) conformation [30]. Conversely, AMP, which induces the R state, favours phosphorylation.…”
Section: -mentioning
confidence: 99%